Status of cytoreductive surgery and hyperthermic intraperitoneal chemotherapy in patients with peritoneal carcinomatosis from colorectal cancer - Yang, Seung Yoon (J Gastrointest Oncol, 2019)
Peritoneal carcinomatosis (PC) was previously considered an incurable disease with a poor survival outcome. As our understanding of its biology evolved, the paradigm of the management of PC from colorectal cancer (CRC) has changed, including the combination of macroscopic disease control, cytoreductive surgery (CRS), maximal regional chemotherapy to treat residual microscopic disease, and hyperthermic intraperitoneal chemotherapy (HIPEC). As with many surgical innovations, CRS with HIPEC has evolved faster than data to support it, leaving many skeptics and critics. This review highlights the recent evidence of current practice and outcome of CRS with HIPEC. Furthermore, it also summarizes the ongoing clinical trials and potential future progress of this treatment modality.